"That's My Sad, It's Not Your Sad": Love, Loneliness, and Communication in The Broom of the System by David Foster Wallace. Issue 1 (1st January 2020) - Mayo, Rob
ABSTRACT: Wallace's first novel remains critically neglected, due in part perhaps to his misrepresentation and disavowal of his early work after the success of Infinite Jest . His debut novel, The Broom of the System, is not merely "juvenilia" but in fact provides the foundations for understanding Wallace's career-long thematic focus on loneliness and other dysphoric conditions such as depression and boredom. This essay challenges readings of the novel which posit Lenore as the vehicle for Wallace's engagement with Wittgenstein's philosophy, and demonstrates the centrality of Rick Vigorous as both the novel's narrator and a manifestation of loneliness. This reading examines critically overlooked aspects of the novel, including metafictional elements and tragic members of the Beadsman family, demonstrating Wallace's fundamental concern with love and loneliness and opening up new avenues of critical inquiry.